Improving Public Health in Ohio by Refining Measurement of Paid Sick Leave - Patricia Stoddard-Dare; LeaAnne DeRigne (Ohio Journal of Public Health, 2025)
Paid sick leave is an active health policy consideration. Publicly and privately funded datasets have been used to evaluate paid sick leave in relation to business, employment, and health outcomes. These findings have informed 40 states and localities that have passed legislation since 2006 that requires paid sick leave to be available to certain employees. During the same time frame, 24 states, including Ohio, enacted preemptive laws prohibiting the adoption of a local paid sick leave regulation by a local city or county. The present investigation organizes, compares, and evaluates the implications of how paid sick leave is measured in 9 datasets. Findings from this investigation can be used to refine the measurement of paid sick leave to inform this ongoing public health policy debate in Ohio and countrywide.
Keywords: Measurement; Paid sick leave; Paid sick days; Health policy